2019
DOI: 10.2478/quageo-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Sentimentality versus Transformation of the Historical Traditional Rural Landscape (A Case Study: The Landscape of Dutch Law Settlement in Poland)

Abstract: The study concentrated on social attitudes towards landscape heritage and the how the place of living was perceived in the context of the transformation of the rural landscape that is currently taking place. The following question was formulated: Are individuals’ approaches to landscape and their attachment to their place of living essential in terms of landscaping and future landscape changes? The research revealed that individual perceptions of rurality and the historical traditional rural landscape (HTRL) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(58 reference statements)
0
6
0
1
Order By: Relevance
“…Such an approach can also account for contextual relations and levels of trust in formal or state institutions. Broader social change can also affect the agricultural practices associated with particular regions, cultures or traditions, but may be inhibited by the exclusion of options at national level for their inconsistency with traditional land uses (Jones, 1991;Markuszewska, 2019;Solymosi, 2011). This may imply a role for 'centralised flexibility' that enables decentralisation while also guaranteeing scope for adaptations at local scales -or, as Pe'er et al (2020) suggest, local experimentation within a rigorous EU-wide monitoring and payment framework.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach can also account for contextual relations and levels of trust in formal or state institutions. Broader social change can also affect the agricultural practices associated with particular regions, cultures or traditions, but may be inhibited by the exclusion of options at national level for their inconsistency with traditional land uses (Jones, 1991;Markuszewska, 2019;Solymosi, 2011). This may imply a role for 'centralised flexibility' that enables decentralisation while also guaranteeing scope for adaptations at local scales -or, as Pe'er et al (2020) suggest, local experimentation within a rigorous EU-wide monitoring and payment framework.…”
Section: Resultsmentioning
confidence: 99%
“…Due to uneconomic farming, the areas of Ziemia Kłodzka depopulated and entire villages transformed into summer resorts [67,68]. It is worth noting that the results of the survey on the preferences of visitors staying in holiday villages showed that respondents when choosing a village gave priority to its traditional character [9][10][11][12][13]64,67,69]. Research into agritourism also indicated that its development is influenced both by the so-called natural attractiveness factor (natural and landscape values) and cultural attractiveness (historical monuments, regional buildings) [7,9,60].…”
Section: Resultsmentioning
confidence: 99%
“…The sixth and last category-agritourism space: greenery and details-assesses the condition (quality) of the agritourism space where guests stay. This category relates to determining the agricultural past of the farm and the preservation of its rural character [4,13,14,28,53,54,57,59,61,63,64].…”
Section: Assessment Categories For Agritourism Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Однак, крім надбань польських учених щодо реформування місцевого самоврядування в Польщі, не слід нехтувати їхніми напрацюваннями із цієї тематики на прикладі інших розвинених країн, зокрема: Нідерландів [51], Німеччини [30] Є теоретико-методологічні та прикладні практичні підстави вважати, що в Україні головною причиною проблем, пов'язаних із формуванням і функціонуванням ОТГ, стала недостатня увага, яку було приділено ідентифікації вихідних умов для формування спроможних ОТГ. На жаль, широкому загалу це стало зрозумілим тільки після двох-трьох років функціонування створених ОТГ (особливо, що стосується сільських і селищних ОТГ).…”
unclassified